2014
DOI: 10.1007/jhep07(2014)133
|View full text |Cite
|
Sign up to set email alerts
|

Symplectic deformations of gauged maximal supergravity

Abstract: Abstract:We identify the space of symplectic deformations of maximal gauged supergravity theories. Coordinates of such space parametrize inequivalent supergravity models with the same gauge group. We apply our procedure to the SO(8) gauging, extending recent analyses. We also study other interesting cases, including Cremmer-Scherk-Schwarz models and gaugings of groups contained in SL(8, R) and in SU * (8).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
195
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(202 citation statements)
references
References 74 publications
5
195
1
1
Order By: Relevance
“…For the S 7 case, we found that there were no global solutions other than that giving the standard ω=0 geometrical prefixitalicSO(8) gauging of []. It was shown in [] that the gauging parameters should be continuous, thus even for the prefixitalicSO(4) case we seem to be missing some of the possible gaugings.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For the S 7 case, we found that there were no global solutions other than that giving the standard ω=0 geometrical prefixitalicSO(8) gauging of []. It was shown in [] that the gauging parameters should be continuous, thus even for the prefixitalicSO(4) case we seem to be missing some of the possible gaugings.…”
Section: Discussionmentioning
confidence: 98%
“…The de Wit–Nicolai theory famously arises as a consistent truncation of eleven‐dimensional supergravity on a round seven‐sphere . A natural question is whether all the theories in the family can be realised in higher‐dimensional supergravity, or, more generally, as string or M theory backgrounds, a possibility that has been investigated by a number of authors …”
Section: Introductionmentioning
confidence: 99%
“…The gaugings of supergravities have revealed the importance of the choice of duality frame, in the sense that the space of consistent deformations depends on that choice (see [18,19] and the recent analysis in [20,21]). In order to take this feature into account, a formalism has been developed in [22][23][24][25], called the "embedding tensor" formalism.…”
Section: Jhep02(2018)064mentioning
confidence: 99%
“…It is in this sense that these variants of the double potential formalism are equivalent, but of course not locally so. The third and fourth set of equations can be written as 20) where …”
Section: Jhep02(2018)064mentioning
confidence: 99%
“…symplectic transformations also provide an example of pseudo-dualities in supergravity [54] 3 this coset was recently exploited in the analysis of the so-called symplectic deformations of gauged N = 8, D = 4 supergravity [55], later extended to other supergravity theories 4 We will always consider the "large, real charge" supergravity limit within BHQC. In the case of (dyonic) quantized charges, the analysis of FTSs is more complicated, and a full classification of U-duality orbits is not even currently available (for some advances along this venue, and lists of references, cf., e.g., [25,57]).…”
Section: Introductionmentioning
confidence: 99%